Habitat Condition and Diversity of Macrozoobenthos and Nekton Species in The Laut Mati Tasi Ana Rote Ndao Regency, East Nusa Tenggara - Sombo, Imelda; Elvis Albertus Bin Toni; Yohanis Nurak Siwa (International Journal of Science, Technology & Management, 2020)
Abstract Lake Laut MatiTasi Ana is located in Daeurendale Village, Landuleko Sub-District of Rote Ndao Regency East Nusa Tenggara Province. The conditions and characteristics of water habitat of this Lake greatly affect the diversity of existing biota. Insofar, data and information about the diversity of macrozoobenthos and nekton in this lake arestill are not available. This study aims to identify the diversity of macrozoobenthos and nekton that exist in the lake as well as their habitat condition parameters. The samples of data were collected from four predetermined stations of coordinate points (1.Oemasapoka, 2.Olokama, 3.Kaluoen, 4. Lolokaslain) by using cruise method. The study found that in this lake there exist eight species of macrozoobenthos which include Parathelphusaconvexa, Melanoidesturricula, M. tuberculata, M. maculata, Neritaundata, Mytilusedulis, Acar squamosa, Cerastodermaglaucum. Most of those macrozoobenthos belong to Gastropod class. In addition, there are four species of nekton namely Oreochormis niloticus, O. mossambicus, Paracheirodon simulans, Channa sp. All of these nektons are found only in station 1 (Oemasapoka). It is conceivable asthe watersalinity of this station is 30 0/00 and the pH level is 9.29. Such condition allows the existence of the nektons.